PENGARUH METODE LATIHAN SMALL-SIDED GAMES TERHADAP DAYA TAHAN ANGGOTA EKSTRAKURIKULER FUTSAL SMP NEGERI 2 CIBITUNG - Irpan Abdurahman; Manaf Dermawan; Akbar Maulana; Erpin Abdalah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low endurance level of futsal extracurricular members at SMP Negeri 2 Cibitung, as indicated by students experiencing fatigue quickly during training sessions and matches. In addition, the training methods applied were less varied and not specifically focused on improving endurance. This study aimed to determine the effect of the Small-Sided Games training method on the endurance of futsal extracurricular members at SMP Negeri 2 Cibitung. This study employed an experimental method using a One Group Pretest-Posttest Design. The sample consisted of 16 students selected through a total sampling technique. Endurance was measured using the PACER Test (Progressive Aerobic Cardiovascular Endurance Run). Data were analyzed using normality tests and hypothesis testing through the Paired Sample t-Test with SPSS version 25. The results showed that both pretest and posttest data were normally distributed. The mean pretest score was 13.80 and increased to 19.20 in the posttest. The Paired Sample t-Test revealed a significance value of 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Small-Sided Games training method had a significant effect on improving the endurance of futsal extracurricular members at SMP Negeri 2 Cibitung.